Gen Z in Investing: Exploring Intentions Through the Theory of Planned Behavior - Susada, Jilla Mae (Journal of Interdisciplinary Perspectives, 2025)
This study examines the investment intentions of Generation Z, focusing on BSBA students in Cateel, Davao Oriental, Philippines, through the Theory of Planned Behavior (TPB). It explores how attitudes, subjective norms, and perceived behavioral control influence financial decisions amid evolving digital investment trends. Employing a quantitative descriptive-comparative design, data were gathered from 191 students via stratified random sampling. Surveys were used as the primary tool, and results were analyzed using ANOVA and multiple regression through SPSS. Findings reveal that perceived behavioral control, linked to financial literacy and self-efficacy, is the strongest predictor of investment intention. At the same time, attitudes are generally positive and subjective norms have a moderate influence. Significant differences were observed across age and year level, but not gender. The study recommends integrating financial literacy into academic programs and enhancing regulatory measures for digital investment platforms.